Rutting assessment of crumb rubber modifier modified warm mix asphalt incorporating warm asphalt additive - Batari, Ahmad; Aman, Mohamad Yusri; Saeed, Saeed Modibbo; Ahmed, Tijjani Yero (Fast Track Publication, 2017)
Warm Mix Asphalt (WMA) as a green technology, permits production of asphalt mixtures at lower temperatures compared to conventional HMA; emissions and energy consumption reduction, were among the key success of this technology, thus, enhancing social, economic, and environmental sustainability. But due to the reduced production temperature, WMA are more prone to rutting, to improve the rutting resistance of WMA mixtures and minimize pollution resulting from waste rubber tire. Therefore, the effect of wet processed Crumb Rubber Modifier (CRM) on rutting depth of WMA mixtures incorporating 2.5% Sasobit by weight of base binders were assessed in the laboratory. In this study, the asphalt mixtures were fabricated in accordance with Superpave, using; crush granite aggregate of 9.5mm NMAS and the four binders that were produced by blending the PG 64 binder with different contents of 40 mesh size CRM (0%, 5%, 10%, and 15%, by weight of the base binder). Rutting depths of the mixtures were assessed on 150mm diameter and 70mm thick cylindrical samples using wheel tracker, the wheel tracking test were carried out at 45oC and 60oC, in accordance with BS 598 Part 110 (1998). Based on the results of wheel tracking tests, CRM could improve the resistance of the WMA mixtures to rutting. It was also found from statistical Analysis of Variance (ANOVA), that the two influence factors; CRM, and the test temperature both having p-values less than the assumed significance at 95% confidence level, therefore they have significant effect on rutting in WMA.